As vozes das crianças sobre o livro de literatura infantil com temática indígena: entre o verbal e o visual - Oliveira, Manoilly Dantas de (2020)
This dissertation, entitled “Children’s voices on the children’s literature book with na indigenous theme: between the verbal and visual”, aims to investigate the possible contributions of the children’s literature book with indigenous themes in the training of school readers. The specific objectives are: to investigate children’s literature with na indigenous thematics and their graphic design; know the children’s responses to the children’s literature book with an indigenous thematic; identify the horizon of expectations about the indigenous people before and after the reading sessions. It’s understood by children’s literature with indigenous themes and literature Works that focus on aspects of the history and culture of the indigenous people of Brazil. It’s included as indigeonus productions the ones which are from indigenous authorship, and indigenists, books written by non-indigenous people. We defend the presence of children’s literature books with indigenous themes at school as a path to discuss the indigenous theme in an updated way, collaborating with the implementation of the Law nº 11.645, of March 10, 2008, which establishes the study of the indigenous theme as mandatory in educational institutions. It was used as a theoretical reference of Freire (2011), Martins (2006) and Smith (1989), to reflect about Reading; Amarilha (2009), Coelho (2000), Culler (1999), Compagnon (2009), Jauss (2002) and Zilberman (1989), about the literature and aesthetics of reception; Hendel (2006), Moraes (2008), Dondis (2015) and Lins (2003), about illustration and graphic design; Bonin (2009; 2008), Graúna (2013), Thiel (2012), about literature with na indigenous thematic. It was carried out a qualitative research with a pedagogical intervention. The reading sessions happened in a public school in the North Zone of Natal/RN. It’s part of the literary corpus the Works: A boca da noite (2016), by Cristino Wapichana and illustrated by Graça Lima; A mulher que virou urutau (2011), by Olívio Jekupé and Maria Kerexu, illustrated by Taísa Borges; Cobra-grande: histórias da Amazônia by Sean Taylor and illustrated by Fernando Virela; Histórias de índio (2016), written by Daniel Munduruku and illustrated by Laurabeatriz; and Meu vô Apolinário: um mergulho no rio da minha memória (2005), by Daniel Munduruku and illustrated by Rogério Borges. Twenty-five subjects participated in the nine Reading sessions, aged between 10 and 13 years old, from a Year 5 classroom of the elementary school. The sessions were organized according to the methodology of scaffolding (GRAVES; GRAVES, 1995), in which it was tried to read the books of literature with an indigenous theme, considering verbal text and the components of graphic project such as the cover, the paratexts, the typography and illustrations. For data collection, it was used participant observation, the field diary, the recordings of the reading sessions on vídeo and semi-structured interviews with the subjects, recorded on audio. The results of the study shows that, in order to read children’s literature books with an indigenous theme, it is necessary to consider the literary text and the graphic design of the book, since the components of the graphic design contributes to the comprehension of the book. The investigation also highlighted that the reading of these books might promote reflection about the stereotypes, as well as the knowledge about the culture of diferente Brazilian indigenous people. The research subjects were unaware of these productions, which reveals the incipient presence of their books in the classroom. The investigation reaffirms the importance of children’s literature with na indigenous theme for greater knowledge of considering verbal, visual and plastic language when reading these books.